The Impact of the Basel III Rules on the Capital Structure of Major Brazilian Banks - Nunes, Rodolfo Vieira (2023)
Purpose: Financial institutions in Brazil had to follow the Central Bank's determinations regarding the rules that regulate the global financial system. From this perspective, this study aims to analyze the Basel Index's influence on the main banks' leverage.Methodology: Thus, archival, descriptive, and quantitative research on Basel III was carried out, using a sample of 09 Brazilian banks during the years 2012 through 2016. The data were obtained through the Thomson Reuters Eikon and Brazil Central Bank databases, and an OLS regression (Ordinary Least Squares) was applied to the dependent variable leverage.Findings: The results showed a positive relationship between the Basel Index and the size of financial institutions in Brazil. This finding suggests that Brazilian banks suffer direct impacts on the capital structure with regard to regulations and their size as the concentration of the sector produces a structure that seeks the efficiency of bank activities.Originality/value: The study contributes to the literature on the subject, with respect to the capital structure and mainly because it is related to the risk factors and reference equity in this sector since the findings indicate that there are factors that have not yet been explored in the capital structure of the banking sector. Such factors have to explore, as well.